Monobenzone, a Novel and Potent KDM1A Inhibitor, Suppresses Migration of Gastric Cancer Cells - Ma, Peizhi; Jia, Gang; Song, Zhiyu (Frontiers in Pharmacology, 2021)
Lysine-specific demethylase1 (KDM1A) is generally highly expressed in various cancer tissues, and promotes the initiation and development of cancers via diverse cellular signaling pathways. Therefore, KDM1A is a promising drug target in many cancers, and it is crucial to find effective KDM1A inhibitors, while none of them has entered into market. With the help of compound library, monobenzone, a local depigmentor using as a treating over-pigmentation in clinic, was characterized as an effective KDM1A inhibitor (IC50 = 0.4507 μM), which may competitively inhibit KDM1A reversibly. Further cellular study confirmed that monobenzone could inhibit the proliferation of gastric cancer cell lines MGC-803 and BGC-823 with IC50 as 7.82 ± 0.55 μM and 6.99 ± 0.51 μM, respectively, and erase the substrate of KDM1A, H3K4me1/2 and H3K9 me2, and inhibit the migration of gastric cancer cell by reversing epithelial–mesenchymal transition (EMT). As the structure of monobenzone is very simple and small, this study provides a novel backbone for the further optimization of KDM1A inhibitor and gives monobenzone potential new application.